2012
DOI: 10.1038/npp.2012.252
|View full text |Cite
|
Sign up to set email alerts
|

Using Standardized fMRI Protocols to Identify Patterns of Prefrontal Circuit Dysregulation that are Common and Specific to Cognitive and Emotional Tasks in Major Depressive Disorder: First Wave Results from the iSPOT-D Study

Abstract: Functional neuroimaging studies have implicated dysregulation of prefrontal circuits in major depressive disorder (MDD), and these circuits are a viable target for predicting treatment outcomes. However, because of the heterogeneity of tasks and samples used in studies to date, it is unclear whether the central dysfunction is one of prefrontal hyperreactivity or hyporeactivity. We used a standardized battery of tasks and protocols for functional magnetic resonance imaging, to identify the common vs the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 45 publications
7
115
0
1
Order By: Relevance
“…Our findings of increased functional connectivity in the primary sensory-motor area as well as in the dlPFC, which is consistently involved in the cognitive control of motor behavior, 21 are consistent with a preparation or readiness activation of the motor system in muscular resistance. Moreover, Hamilton et al 22 and Korgaonkar et al 23 propose the dlPFC is involved in the appraisal of negative emotional inputs (appraisal being deregulated in major depressive disorder). In the context of our shoulder apprehension videos, the increase in dlPFC might indicate an increased reappraisal of negative information related to the negative valence of the videos, in addition to its role in modulating pre/motor regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of increased functional connectivity in the primary sensory-motor area as well as in the dlPFC, which is consistently involved in the cognitive control of motor behavior, 21 are consistent with a preparation or readiness activation of the motor system in muscular resistance. Moreover, Hamilton et al 22 and Korgaonkar et al 23 propose the dlPFC is involved in the appraisal of negative emotional inputs (appraisal being deregulated in major depressive disorder). In the context of our shoulder apprehension videos, the increase in dlPFC might indicate an increased reappraisal of negative information related to the negative valence of the videos, in addition to its role in modulating pre/motor regions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous fMRI studies have revealed that the frontal lobe is associated with motor, perceptual and cognitive functions. [78][79][80][81][82] The CC modulates cognitive processes and information transfer between hemispheres. 83 One DTI study demonstrated that abnormalities in the structural integrity of the anterior genu of the CC may contribute to impairment of interhemispheric connectivity in medication-naive patients with MDD.…”
Section: Fractional Anisotropy Reductions In the Corpus Callosummentioning
confidence: 99%
“…Structural alterations in the prefrontal cortex, particularly the anterior cingulate, and subcortical hippocampal, amygdalar, thalamic, and striatal/ pallidal centers are consistently implicated (Drevets et al, 2008;Lorenzetti et al, 2009;Schmaal et al, 2015). Lesion and functional imaging studies show these regions form networks governing mood regulation, reward sensitivity, and emotion (Koenigs and Grafman, 2009;Ochsner et al, 2012;Hamilton et al, 2013;Korgaonkar et al, 2013). Symptoms of depression such as amotivation, anhedonia, apathy, and rumination are linked to functional disturbances in the ventral striatum/ pallidum specifically (Disner et al, 2011;Ochsner et al, 2012;Kuhn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%